Transmission of bone conducted sound – Correlation between hearing perception and cochlear vibration - Eeg-Olofsson, Måns; Stenfelt, Stefan; Taghavi, Hamidreza; Reinfeldt, Sabine; Håkansson, Bo; Tengstrand, Tomas; Finizia, Caterina (Hearing research, 2013)
The vibration velocity of the lateral semicircular canal and the cochlear promontory was measured on 16 subjects with a unilateral middle ear common cavity, using a laser Doppler vibrometer, when the stimulation was by bone conduction (BC). Four stimulation positions were used: three ipsilateral positions and one contralateral position. Masked BC pure tone thresholds were measured with the stimulation at the same four positions. Valid vibration data were obtained at frequencies between 0.3 and 5.0 kHz. Large intersubject variation of the results was found with both methods. The difference in cochlear velocity with BC stimulation at the four positions varied as a function of frequency while the tone thresholds showed a tendency of lower thresholds with stimulation at positions close to the cochlea. The correlation between the vibration velocities of the two measuring sites of the otic capsule was high. Also, relative median data showed similar trends for both vibration and threshold measurements. However, due to the high variability for both vibration and perceptual data, low correlation between the two methods was found at the individual level. The results from this study indicated that human hearing perception from BC sound can be estimated from the measure of cochlear vibrations of the otic capsule. It also showed that vibration measurements of the cochlea in cadaver heads are similar to that measured in live humans. •Bone conducted sound stimulation was conducted at four human skull positions.•Cochlear vibration was compared to hearing perception in the same individuals.•Cochlear vibration and hearing perception corresponded well on a group level.•The correlation was low on the individual level.•The vibration pattern between live humans and cadavers are similar.